Investigation of brass microstructure and mechanical properties using metal casting - Nur Hamizah, Minhat (2010)
Brass is a alloying of cooper and zine, alpha (a) brass are quite soft and ductile, the ductility of the a brasses actually increased zinc content. The maximum strength of brass is 538 Mpa attained at 44wt% zinc. while most brasses are nit normally ranked as 'heat tratable', some brasses of very closely controlled composition are cast or hot worked in the duplex a/B state and the annealed at about 450 C to convert the microstructure to an single phase of better resistance to corrosion by dezincification in aggressive supply waters.